Developments in C-s-corrected STEM - Lupini, A; Krivanek, O; Dellby, N; Nellist, P; Pennycook, S (2001)
The new corrector of spherical aberration (C-s) we have built for a Scanning Transmission Electron Microscope (STEM) is described. We have recently installed such a corrector in a dedicated 100 kV STEM at Oak Ridge National Laboratory and the first results are presented. We conclude by discussing upcoming developments.